2008
DOI: 10.1021/es071328w
|View full text |Cite
|
Sign up to set email alerts
|

Straining of Nonspherical Colloids in Saturated Porous Media

Abstract: We explore the effects of colloid shape on straining kinetics by measuring the filtration of spherical and nonspherical colloids within saturated columns packed with quartz sand. Our observations demonstrate that the transport of peanut-shaped colloids matches the transport of spherical colloids with diameters equal to the minor-axis length of the peanut-shaped colloids. The straining rates of the spherical colloids vary linearly with the ratio of colloid diameter (d(p)) to sand-grain diameter (d(g)) for 0.008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 26 publications
4
89
1
Order By: Relevance
“…In addition, straining of colloids in the saturated system also depends on solution properties, colloid size, colloid shape, colloid size distribution as well as grain size and heterogeneity [2,3,5,6,71,85,86]. The straining of colloids were more dominant for large, irregular shape, and multi-disperse colloids [84][85][86].…”
Section: Attachment Of Colloid By Strainingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, straining of colloids in the saturated system also depends on solution properties, colloid size, colloid shape, colloid size distribution as well as grain size and heterogeneity [2,3,5,6,71,85,86]. The straining of colloids were more dominant for large, irregular shape, and multi-disperse colloids [84][85][86].…”
Section: Attachment Of Colloid By Strainingmentioning
confidence: 99%
“…The straining of colloids were more dominant for large, irregular shape, and multi-disperse colloids [84][85][86]. Straining of colloids in the unsaturated porous media become very complex due to the presence of gaseous phase.…”
Section: Attachment Of Colloid By Strainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive observation of platelet movement in interstices of microfilter chips representing PRP filters revealed that platelets do not rotate when passing through filter at creeping/Stokesian flow conditions, i.e., Re<<1 (Javadpour 2006). The nonrotating movement of platelets may be explained by the interesting work of Xu et al (2008). Xu et al (2008) suggested that high contraction ratio (H/r; where H and r are the half-widths of the domain at the widest and narrowest parts of the pore channel, respectively) causes large velocity difference that may rotate spheroids.…”
Section: Platelet Shape Factormentioning
confidence: 99%
“…The nonrotating movement of platelets may be explained by the interesting work of Xu et al (2008). Xu et al (2008) suggested that high contraction ratio (H/r; where H and r are the half-widths of the domain at the widest and narrowest parts of the pore channel, respectively) causes large velocity difference that may rotate spheroids. For example, H/r = 60/0.95 is needed to induce rotation at creeping/Stokesian flow condition.…”
Section: Platelet Shape Factormentioning
confidence: 99%